Revitalizing the AZT Through of the Selenium: An Approach in Human Triple Negative Breast Cancer Cell Line - Wagner, Mônica Silveira; Schultze, Eduarda; Oliveira, Thais Larre; de Leon, Priscila Marques Moura; Thurow, Helena Strelow; Campos, Vinicius Farias; Oliveira, Isabel; Souza, Diego de; Rodrigues, Oscar Endrigo Dorneles; Collares, Tiago; Seixas, Fabiana Kömmling (Frontiers in Oncology, 2018)
Triple-negative breast cancer represents about 15% of all cases of breast cancer, and still represents a therapeutic challenge. 3’-Azido-3’-deoxythymidine (AZT) is a nucleoside reverse transcriptase inhibitor with antitumor activity. Chalcogenides compounds, such as selenium, are very important intermediates applied in organic synthesis. Our objective was to investigate the effect and the underlying cell death mechanisms of AZT and its derivatives, in human breast cancer cell lines. The inhibitory effect of AZT and derivatives (1072, 1073 and 1079) was determined by MTT assay (0.1, 1, 10, 50 and 100 µM for concentrations and times 4, 24, 48 and 72h) and Live/Dead in tumor cell lines MCF-7, MDA-MB 231 and also in non-tumor cell line CHO. Gene expression profiles related to apoptosis were investigated by qRT-PCR and induction of apoptosis was investigated by flow cytometry. MTT and Live/Dead assays showed that AZT derivatives decreased the rate of cell proliferation at concentrations of 50 and 100 µM in tumor cell lines MCF-7 and MDA-MB 231 while the commercial AZT presented a low antitumoral potential in all strains tested. In flow cytometry analysis we demonstrated that derivatives of AZT induced apoptosis, with an increase in both initial and late stages in both tumor cell lines evaluated, especially in MDA-MB 231. Our data show that the AZT derivative 1072 increased the expression of transcripts of the genes caspase 3 and 8 in MDA-MB 231 cell line when compared to control, suggesting that the extrinsic pathway of apoptosis was activated. In conclusion, derivatives of AZT, especially 1072, induce cytotoxicity in vitro in the triple negative breast cancer cell line through activation of the extrinsic pathway of apoptosis. These compounds containing selenium in its formulation are potential therapeutic agents for breast cancer.